Pullulan: an advantageous natural polysaccharide excipient to formulate tablets of alendronate-loaded microparticles - Luana Mota Ferreira; Aline de Arce Velasquez; Scheila Rezende Schaffazick; Letícia Cruz (Universidade de São Paulo, 2015)
This work reports the preparation of tablets by direct compression of sodium alendronate-loaded microparticles, using pullulan as filler. The tableting properties of pullulan were compared with those of microcrystalline cellulose and lactose. Pullulan tablets showed low variations in average weight, thickness and drug content. Moreover, these tablets exhibited a higher hardness compared to the other excipients. In vitro release studies showed that only pullulan was capable to maintain gastroresistance and release properties of microparticles, due to its ability to protect particles against damage caused by compression force. Thus, pullulan was considered an advantageous excipient to prepare tableted microparticles.